2019
DOI: 10.1016/j.jconrel.2019.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Combining vascular targeting and the local first pass provides 100-fold higher uptake of ICAM-1-targeted vs untargeted nanocarriers in the inflamed brain

Abstract: New advances in intra-arterial (IA) catheters offer clinically proven local interventions in the brain. Here we tested the effect of combining local IA delivery and vascular immunotargeting. Microinjection of tumor necrosis factor alpha (TNFα) in the brain parenchyma causes cerebral overexpression of Inter-Cellular Adhesion Molecule-1 (ICAM-1) in mice. Systemic intravenous injection of ICAM-1 antibody (anti-ICAM-1) and anti-ICAM-1/liposomes provided nearly an order of magnitude higher uptake in the inflamed vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 33 publications
1
29
0
Order By: Relevance
“…Bioconjugation methods for attaching antibodies to liposomal surfaces typically involve covalent bonding of the antibody to the liposome surface [91]. Much of the current literature focuses on examining new antibody designs or antibody-drug variations for therapeutic applications [92][93][94][95]. For example, Nikkhoi and colleagues explored the development of a bivalent, bispecific VHH-domain HER2-antibody fragment attached to liposomes to treat HER2-positive breast cancer [85].…”
Section: Antibody-liposome Bioconjugates (Immunoliposomes)mentioning
confidence: 99%
“…Bioconjugation methods for attaching antibodies to liposomal surfaces typically involve covalent bonding of the antibody to the liposome surface [91]. Much of the current literature focuses on examining new antibody designs or antibody-drug variations for therapeutic applications [92][93][94][95]. For example, Nikkhoi and colleagues explored the development of a bivalent, bispecific VHH-domain HER2-antibody fragment attached to liposomes to treat HER2-positive breast cancer [85].…”
Section: Antibody-liposome Bioconjugates (Immunoliposomes)mentioning
confidence: 99%
“…Marcos-Contreras et al reported that conjugating anti-ICAM-1 or anti-VCAM-1 antibodies to liposomes results in efficient cerebral accumulation of the conjugated-liposomes through active targeting of endothelial cells. Superior penetration rates were measured when compared to transferrin-conjugation, another commonly used strategy to enhance nanoparticle CNS penetration (Marcos-Contreras et al, 2019. Although CNS targeting was improved, some off-target effects were still detected in these approaches, such as nanoparticle accumulation in the lungs.…”
Section: Cell Targeting Using Nanoparticles To Modulate Neuroinflammamentioning
confidence: 99%
“…While a significant body of literature supports the utility of affinity targeting of PECAM‐1 and ICAM‐1 for endothelial drug delivery, 13,14,16,19,24,27,29‐33 much of this work has focused on multivalent polymeric, liposomal, and protein nanoparticles, and relatively few studies have investigated the cell types targeted in vivo 28 . To determine suitability for endothelial surface delivery, we first measured the distribution of intravenously injected, fluorescent PECAM and ICAM antibodies using flow cytometry of disaggregated organs.…”
Section: Resultsmentioning
confidence: 99%